Efektivitas Edukasi Gizi melalui Media Display Isi Piringku terhadap Pengetahuan Gizi Anak Sekolah Dasar Pangeran 3 Banjarmasin - Mawaddah, Annida; Fatimah, Siti; Rezki, Muhammad Bayu; Paramitha, Dewi Setya; Rahayu, Suci Fitri (Universitas Tadulako, 2025)
School kids' nutritional understanding is still rather limited; they need engaging and straightforward learning materials; the display media isi piringku serves as a tool to help students grasp the notion of balanced nutrition in a more clear and efficient manner. The goal of this research is to assess how well the isi piringku nutrition education program uses the display media to teach elementary school students about nutrition. Using a quasi-experimental design with a one-group pre-test post-test model, the methodology collected data from 30 students in the fourth and fifth grades who satisfied the inclusion and exclusion criteria using a purposive sampling method. The sample size was determined using the Wilcoxon test formula. Data collection methods were used to compare knowledge and behavior before and after the intervention using univariate and bivariate analysis with the Wilcoxon test. In univariate and bivariate analysis of the knowledge variable, the study showed the findings of the Wilcoxon test to have a p value of 0.317 ( 0.05), while the behavioral value had a p value of 0.003 ( 0.05). The study's findings indicated that students' behavior changed significantly in a more favorable way after they got balanced nutrition education through the display media